Using media reports to analyze the spatio-temporal evolution of carbon dioxide management development in China - Gao, Ruosu; Yang, Kunshu; Qin, Chuan; Wan, Yunshan (Frontiers in Ecology and Evolution, 2022)
Over the past few decades, the carbon dioxide (CO2) emissions management problem has attracted global attention. China is transitioning to carbon neutrality and experienced rapid development in low-carbon management. However, current studies have limited understanding of the evolutionary process and development issues at a macro-level, which may hinder the structural reformation of stepwise carbon-neutral development. This study used the content analysis method to process and code reports from China's most prominent news media, Xinhua News Agency, to identify China's low-carbon evolution and development issues. The results depict a trend of gradually increasing carbon management within China and highlight the staged development features. 2010 and 2021 are the critical nodes of carbon emissions management in China, representing the two primary actions of low-carbon pilot city projects and the carbon-neutral construction. However, the results also reveal the uneven development problem of China's carbon management behind the rapid transition. The government is the primary participant in carbon management, but the participation of firms and the public is relatively low. The power industry implements the highest amount of carbon management actions, but less attention is paid to other sectors with high carbon emissions. Report tones on environmental protection and green technology have gradually declined, while the tone on economic and social development has increased. There are evident differences in the number of carbon management measures implemented between regions. The southeast coastal regions report more management numbers than China's central and western regions. The top three provinces (or municipalities) are Beijing (131), Shanghai (93), and Guangdong (78). From an industry perspective, more-reported regions have implemented carbon management measures in more industries than less-reported regions. This study provides a distinctive contribution to the theoretical work on China's carbon emissions regulation and the emerging planning and management mechanisms.